Efficacy of Extracorporeal Shock Wave Therapy in Neck and Shoulder Pain Syndrome - Kim, Joon Yub; Kim, Jae Yoon; Yoon, Jong Pil; Chung, Seok Won; Kim, Dong-Hyun; Won, Yoo-Sun (The Korean Journal of Sports Medicine, 2020)
Purpose: The aim of current study is to verify the efficacy of extracorporeal shock wave therapy (ESWT) in neck and shoulder pain syndrome. Methods: We enrolled 23 patients with neck and shoulder pain syndrome (mean age, 55±16 years; onset, 12.65±8.90 months) who underwent ESWT from July to December 2019. ESWT (4 to 5 bar or 0.23–0.45 mJ/mm 2 , 1,500 to 2,000 times/region, 7 Hz) was performed at least 4 consecutive times per week. Evaluated outcomes were visual analogue scale (VAS) of pain and tenderness, neck disability index (NDI), and shoulder passive range of motion (ROM; forward flexion [FF], external rotation at neutral [ER], internal rotation at back [IR]). Pain and tenderness VAS scores were assessed at every follow-up, while NDI and shoulder ROM were evaluated two times before treatment and at the final follw-up (at 4.52±0.73 weeks). Results: The pain VAS score decreased from 5.5±2.4 at first visit to 4.0±1.8 (p=0.001), 3.3±2.1 (p=0.02), and 3.1±2.2 (p=0.29) at the first, second, and third follow-up visits. The tenderness VAS at first visit was 5.98±1.89, which decreased to 5.17±1.83 (p=0.005), 4.61±1.67 (p=0.05), and 4.09±1.92 (p=0.06) at the first, second, and third follow-up visits. NDI was significantly reduced from 18.04±8.86 to 10.04±6.94 at last follow-up (p=0.001) and shoulder ROM was significantly improved after treatment (FF: 159.6°±28.0° to 177.8°±8.5°, p=0.001; ER: 72.2±15.7° to 79.6±2.1°, p=0.02; IR: 10.2±3.49 [T 10] to 6.9±1.7 [T 7], p=0.001). Conclusion: Consecutive ESWT was effective in treating neck and shoulder pain syndrome with functional improvement and pain reduction. Regarding simultaneous pain and tenderness reduction, receiving ESWT two times per week was effective. KCI Citation Count: 0